The Influence of Item Formats when Locating a Student on a Learning Progression in Science - Jing Chen; Amelia Wenk Gotwals; Charles Anderson; Mark Reckase (International Journal of Assessment Tools in Education)
Learning progressions are used to describe how students’ understanding of a topic progresses over time. This study evaluates the effectiveness of different item formats for placing students into levels along a learning progression for carbon cycling. The item formats investigated were Constructed Response (CR) items and two types of two-tier items: (1) Ordered Multiple-Choice (OMC) followed by CR items and (2) Multiple True or False (MTF) followed by CR items. Our results suggest that estimates of students’ learning progression level based on OMC and MTF responses are moderately predictive of their level based on CR responses. With few exceptions, CR items were effective for differentiating students among learning progression levels. Based on the results, we discuss how to design and best use items in each format to more accurately measure students’ level along learning progressions in science.